Extracellular vesicle interactions with the external and internal exposome in mediating carcinogenesis - Kalita-de Croft, Priyakshi; Sharma, Shayna; Sobrevia, Luis [UNESP]; Salomon, Carlos (Elsevier, 2021)
The influence of environmental factors on an individual, from conception onwards, is defined as the exposome. It can be categorized into the external exposome, which includes external factors such as air pollution, chemical contaminants, and diet, and the internal exposome, which is unique to an individual, and involves age, physiology, and their genetic profile. The effect of external exposures on the internal exposome, or genetic profile, can be determined through omics analyses. However, this is often compromised due to low sample quantity and cost. Therefore, identification of other factors that can provide an insight into the cellular profile of an individual, provides an exciting avenue, and an emerging field is that of extracellular vesicles (EVs). Recently, our understanding of how cells can communicate with each other has shifted to recognise the role of EVs. EVs are secreted by all living cells, and have been identified in all biological fluids studied so far. They transport bioactive molecules (e.g., proteins, miRNAs, and DNA), and their release can be regulated by the cellular microenvironment. Analysis of EVs in respond to environmental factors might provide novel insights into the role of tumour EVs in carcinogenesis. Not only will EVs give some insight into the tumour cells themselves but they will also provide a better understanding of how cells communicate with one another, contributing to cancer progression. Moreover, characterising the content and functions of tumour-derived EVs has the potential to overcome the current challenges to improve cancer patient outcomes. For example, the identification of EVs targets for therapeutic interventions and tumour EVs biomarkers could facilitate the development of early screening for several cancers. The aim of this review, thus, is to discuss the overall role of EVs in response to the various external and internal signals in cancer. We will specifically highlight the biogenesis, secretion, and content of EVs in response to oncogenic transformation and metabolic regulators in cancer.
Keywords: Cancer; Exosomes; Exposome; Extracellular vesicles